Passing. De Rihan Yeh - Escalona Victoria, José Luis (Estudios Sociológicos de El Colegio de México, 2020)
Reseña de Passing, Two Publics in a Mexican Border City, de Rihan Yeh. The University of Chicago Press, 2018